EDUKASI GIZI BERBASIS VIDEO LEBIH EFEKTIF DALAM MENINGKATKAN PENGETAHUAN REMAJA MENGENAI GIZI SEIMBANG UNTUK PENCEGAHAN PENYAKIT TIDAK MENULAR - Mahmudah, Umi; Priawantiputri, Witri; Rahmat, Mamat (Media Penelitian dan Pengembangan Kesehatan, 2025)
Adolescents are a vulnerable group when it comes to nutrition-related obesity issues. Obesity is a chronic disease resulting from excessive fat accumulation and is a major risk factor for non-communicable diseases (NCDs). Nutrition knowledge is an important factor as it impacts attitudes and behaviors. This study aimed to assess the differences in nutrition education using video and PowerPoint media on knowledge, attitudes, and behaviors related to balanced nutrition in the prevention of non-communicable diseases among adolescents. The research design was quasi-experiment with a pre-posttest control group design. The study was divided into two groups: the treatment group at SMAN 1 Cimahi, and the control group at SMAN 3 Cimahi in August – November 2024. The results showed a significant effect of nutrition education using video media on knowledge (p = 0.000), attitudes (p = 0.001), and behavior (p = 0.010). The average knowledge score before and after education using video media was 54.24 to 76.97, there was an increase of 22.73 points, the average attitude score was 49.93 to 52.24 increased 2.31 points and the average behavior score was 43.39 to 46.45 increased 3.06 point. The difference in average knowledge was 9.2 points, attitude 1.61 points and behavior 0.67 points higher in the treatment group than the control group. Conclusion: Nutrition education using video media is more effective in improving knowledge of balanced nutrition in the prevention of non-communicable diseases among adolescents compared to PowerPoint media, but it is not more effective in improving attitudes and behaviors related to balanced nutrition.